Project Edubot: Exploring Pedagogical Approaches in High School Robotics Education - Daltro, Isabela Nunes; Santos, João Victor Silva; Sousa, Guilherme Barbosa De; Martins, Rodrigo; Pastrana, M. A.; Baptista, Roberto De Souza (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This study focus on passive and active learning within the context of robotics education on public high schools. By synthesizing research findings and practical insights, this paper offers valuable recommendations for educators aiming to optimize the delivery of robotics education in public high schools, addressing the significance of the utilization of appropriate resources and technologies to support effective instruction. We implemented two distinct teaching methodologies to compare and study students' reactions and learning outcomes: Group A experienced a passive methodology, while Group B engaged with an active methodology. We conducted a survey and the results show that the majority of the students prefer the active approach used in classes.